Negative pole piece and lithium ion battery

By introducing specific additives into the negative electrode sheet of the lithium-ion battery, the negative electrode active material is evenly dispersed, and the problem of dissolution and deposition of the positive electrode transition metal is solved, and the stability and safety of the battery are improved.

CN119725370APending Publication Date: 2025-03-28HUIZHOU EVE POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411962363.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The dissolution and deposition of the positive electrode transition metal in lithium-ion batteries lead to degradation of electrochemical performance and safety risks.

Method used

Additives, such as sodium sulfonate, sulfate and sulfonated olefin, are introduced into the negative electrode active material layer of the negative electrode sheet. Through electrostatic repulsion and steric hindrance effects, the negative electrode active material is uniformly dispersed to form a more uniform active material layer, and promote the uniform deposition of transition metal ions.

Benefits of technology

It improves the electrode performance stability of lithium batteries, uniforms the current density, avoids the risk of lithium dendrites and diaphragm puncture, and enhances the safety and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention specifically discloses a negative pole piece and a lithium ion battery. The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material and an additive, and the mass ratio of the additive to the negative electrode active material is (0.01-5): 100; wherein the additive comprises at least one of sodium sulfonate, sulfate and sulfonated olefin. The method has the advantages that the deposition morphology of transition metal on the surface of the negative electrode is effectively improved, the deposition uniformity of transition metal ions on the surface of the negative electrode is improved, and the cycle performance and the safety performance of the lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode plate and a lithium-ion battery. Background Art

[0002] As an efficient and environmentally friendly energy storage device, lithium-ion batteries have been widely used in electric vehicles, portable electronic devices and other fields. However, lithium-ion batteries also face some problems during use, among which the dissolution of transition metals at the positive electrode is a more serious problem. The dissolution of transition metals not only affects the performance of lithium-ion batteries, but may also cause safety accidents. This is because transition metal ions become metals after being deposited at the negative electrode, which will form a tip discharge and there is a risk of piercing the diaphragm. Therefore, studying the phenomenon and mechanism of transition metal dissolution and deposition in lithium-ion batteries is of great practical significance for improving the electrochemical performance and safety of lithium-ion batteries.

[0003] Some commonly used solutions include: (1) doping or coating the positive electrode material to improve the stability of the positive electrode material; (2) optimizing the electrolyte composition, reducing the electrolyte acidity, and reducing the risk of transition metal precipitation; (3) optimizing the charging and discharging conditions to avoid high voltage, high current and high temperature, thereby slowing down the above factors that accelerate the dissolution and deposition of transition metals. It can be seen that the above methods are all based on the perspective of reducing the dissolution of transition metals, and require changes to the battery materials / electrolytes, or narrowing the battery's use window. There are disadvantages that affect the performance of lithium batteries, such as: the electrolyte components will increase the internal resistance of the battery, and the improvement of the stability of the positive electrode material will reduce the capacity of the battery. In addition, the above methods cannot completely solve the problem of transition metal dissolution and deposition. During the long-term circulation and storage of lithium batteries, transition metal dissolution is still inevitable in lithium batteries. Summary of the invention

[0004] In order to solve the negative impact of positive electrode transition metal dissolution on lithium batteries, the present application provides a negative electrode plate and a lithium-ion battery.

[0005] In a first aspect, the present application provides a negative electrode plate, which adopts the following technical solution:

[0006] A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and an additive, and the mass ratio of the additive to the negative electrode active material is 0.01-5:100;

[0007] Wherein, the additive includes at least one of sodium sulfonate, sulfate and sulfonated olefin.

[0008] The present application introduces the above-mentioned additives into the negative electrode sheet. First, the additives can be adsorbed on the surface of the negative electrode active material, and the negative electrode active material can be evenly dispersed in the negative electrode active material layer through electrostatic repulsion and steric hindrance effect, thereby helping to form an active material layer with more uniform performance on the surface of the negative electrode current collector, which is beneficial to improving the stability of the electrode performance and making the current density more uniform. On the one hand, during the long-term charge and discharge cycle of the lithium-ion battery, the uniform current density helps to promote the transition metal ions dissolved from the positive electrode to be deposited more evenly on the negative electrode surface, avoiding the situation where lithium dendrites pierce the diaphragm. On the other hand, the more uniform current density can avoid local aging and shortened life of the lithium battery under high voltage; second, the additive can effectively reduce the tension of the electrolyte at the electrode surface in the lithium battery, so that the transition metal ions dissolved and lost from the positive electrode can be better spread on the negative electrode surface, increasing the contact area, thereby further improving the deposition uniformity of the transition metal ions on the negative electrode surface, avoiding the situation where lithium dendrites cause tip discharge, helping to reduce the risk of puncture of the diaphragm, and improving the safety of the lithium battery.

[0009] Preferably, the sodium sulfonate salt includes at least one of sodium dodecylbenzene sulfonate, sodium sulfosuccinate, diethyl sulfosuccinate sodium salt, and diamyl sulfosuccinate sodium salt; the sulfate includes at least one of sodium ethylhexyl sulfate, sodium 2-ethylhexyl sulfate, 2-ethylhexyl sulfate ester salt, 2-ethylhexyl sulfate ester salt, lauryl ether sulfate, and polyoxyethylene alkylphenol ether sodium sulfate; the sulfonated olefin includes at least one of propylene sulfonic acid, sulfonamide, and sulfonimide.

[0010] Preferably, in the additive, the mass proportion of the sodium sulfonate salt is 50%-60%.

[0011] Preferably, the additive comprises the sodium sulfonate salt and the sulfate in a mass ratio of 5-6:4-5, or the additive comprises the sodium sulfonate salt and the sulfonated olefin in a mass ratio of 5-6:4-5.

[0012] Preferably, the additive comprises the sodium sulfonate salt, the sulfate and the sulfonated olefin in a mass ratio of 5-6:2-3:2.

[0013] Preferably, the negative electrode active material layer further includes a binder, and the mass ratio of the binder to the negative electrode active material is 0.5-10:100.

[0014] Preferably, the binder includes a first binder and a second binder, the first binder includes at least one of sodium carboxymethyl cellulose and polyacrylic acid; the second binder includes at least one of styrene-butadiene rubber and polyacrylic acid.

[0015] Preferably, the mass ratio of the first binder to the second binder is 10:1-1:10.

[0016] By controlling the usage ratio of the first binder to the second binder and the specific types of the first binder and the second binder, on the one hand, it helps to evenly disperse the active material particles in the negative electrode slurry, and on the other hand, it helps to evenly disperse the additives in the negative electrode slurry, thereby enhancing the promoting effect of the additives on promoting the uniform deposition of the negative electrode slurry, which helps to improve the cycle performance of the lithium battery.

[0017] Preferably, the negative electrode active material layer further includes a conductive agent, and the mass ratio of the conductive agent to the negative electrode active material is 0.5-10:100.

[0018] Preferably, the conductive agent includes a first conductive agent and a second conductive agent, the first conductive agent includes at least one of conductive carbon black, artificial graphite, and acetylene black; the second conductive agent includes at least one of carbon nanotubes and vapor-grown carbon fibers.

[0019] Preferably, the mass ratio of the first conductive agent to the second conductive agent is 20:1-1:1.

[0020] By controlling the usage ratio of the first conductive agent to the second conductive agent and the specific types of the first conductive agent and the second conductive agent, the internal resistance of the negative electrode plate can be significantly reduced, which helps to improve the cycle performance of the lithium battery.

[0021] Preferably, the negative electrode active material layer in the present application is obtained by drying and rolling the negative electrode slurry, and the negative electrode slurry is prepared by a method comprising the following steps:

[0022] S1, mixing the first binder with deionized water to obtain a glue solution; mixing the negative electrode active material with the first conductive agent to obtain a powder mixture;

[0023] S2, mixing the powder mixture with the glue, and then mixing with the second conductive agent, stirring, and continuing to add the additive to obtain a conductive mixture;

[0024] S3, mixing the conductive mixture with the second binder and adjusting the viscosity to 1000-10000 cps to obtain the negative electrode slurry;

[0025] or,

[0026] S1, mixing the first binder with deionized water to obtain a glue solution; mixing the negative electrode active material, the first conductive agent and the additive to obtain a powder mixture;

[0027] S2, mixing the powder mixture with the glue, and then mixing with the second conductive agent, and stirring to obtain a conductive mixture;

[0028] S3, mixing the conductive mixture with the second binder and adjusting the viscosity to 1000-10000 cps to obtain the negative electrode slurry;

[0029] or,

[0030] S1, mixing the first binder with deionized water to obtain a glue solution; mixing the negative electrode active material with the first conductive agent to obtain a powder mixture;

[0031] S2, mixing the powder mixture with the glue, and then mixing with the second conductive agent, stirring, and continuing to add the second binder to adjust the viscosity to obtain a conductive mixture;

[0032] S3, mixing the conductive mixture with the additive, and stirring to obtain the negative electrode slurry.

[0033] The additives in the present application have good applicability in negative electrode slurry, and do not require the use of a specific pulping process, nor do they need to be added in a specific pulping process. Applying them in negative electrode slurry can achieve the corresponding technical effect.

[0034] In a second aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:

[0035] A lithium-ion battery comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet as described above. DETAILED DESCRIPTION

[0036] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0038] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0039] As used herein, "and / or" means one or all of the mentioned elements.

[0040] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0041] All percentages in this application are by weight unless otherwise stated.

[0042] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0043] Example 1

[0044] 1. Preparation of negative electrode slurry

[0045] The negative electrode slurry is prepared by the following steps:

[0046] S1, mixing a first binder with deionized water to obtain a glue solution; mixing the negative electrode active material with the first conductive agent for 30 minutes to obtain a powder mixture;

[0047] S2, mixing the powder mixture with the glue, and then mixing with the second conductive agent, stirring for 3 hours, and continuing to add additives to obtain a conductive mixture;

[0048] S3, mixing the conductive mixture with the second binder and adjusting the viscosity to 4500 cps to obtain negative electrode slurry.

[0049] 2. Preparation of negative electrode

[0050] The above-mentioned negative electrode slurry is evenly coated on the two surfaces of the negative electrode current collector copper foil, dried at 85°C, and then cold pressed, trimmed, cut into pieces, and slit. After slitting, it is dried at 85°C under vacuum conditions for 4 hours, and the pole ears are welded to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. In the negative electrode active material layer, the mass ratio of additives (sodium 2-ethylhexyl sulfate), binder (the mass ratio of carboxymethyl cellulose and styrene-butadiene rubber is 3:8), conductive agent (the mass ratio of conductive carbon black and single-walled carbon nanotubes is 10:1), and negative electrode active material (graphite) is 0.5:1.5:1.5:96.5.

[0051] 3. Preparation of positive electrode

[0052] Positive electrode sheet preparation: positive electrode active material LiMn 0.6 Fe 0.4O4, binder polyvinylidene fluoride (PVDF), conductive agent carbon black, and conductive agent carbon nanotubes are mixed evenly in a weight ratio of 95:2.5:2:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer until the mixed system becomes a positive electrode slurry with uniform fluidity;

[0053] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at 85°C, cold pressed, trimmed, cut and slit, and dried at 85°C for 4 hours under vacuum conditions. The tabs are welded to obtain positive electrode sheets.

[0054] 4. Lithium battery assembly

[0055] The negative electrode sheet, the positive electrode sheet and the isolation film are stacked, packaged, injected with liquid (EC: DMC = 1: 1 vol%), and then packaged again to obtain a lithium-ion battery.

[0056] Example 2

[0057] 1. Preparation of negative electrode slurry

[0058] The negative electrode slurry is prepared by the following steps:

[0059] S1, mixing a first binder with deionized water to obtain a glue solution; mixing the negative electrode active material, the first conductive agent and the additive for 50 minutes to obtain a powder mixture;

[0060] S2, mixing the powder mixture with the glue, and then mixing with the second conductive agent, and stirring for 6 hours to obtain a conductive mixture;

[0061] S3, mixing the conductive mixture with the second binder and adjusting the viscosity to 4500 cps to obtain negative electrode slurry.

[0062] 2. Preparation of negative electrode

[0063] The above-mentioned negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at 85°C, and then cold pressed, trimmed, cut into pieces, and slit. After slitting, it is dried at 85°C under vacuum conditions for 4 hours, and the pole ears are welded to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. In the negative electrode active material layer, the mass ratio of additives (sodium dodecyl sulfate), binder (the mass ratio of polyacrylic acid and styrene-butadiene rubber is 4:8), conductive agent (the mass ratio of acetylene black and vapor-grown carbon fiber is 10:1), and negative electrode active material (the mass ratio of graphite and silicon is: 95:5) is 0.3:1.5:1.5:96.7.

[0064] 3. Preparation of positive electrode

[0065] Positive electrode sheet preparation: positive electrode active material LiMn 0.6 Fe0.4 O4, binder polyvinylidene fluoride (PVDF), conductive agent carbon black, and conductive agent carbon nanotubes are mixed evenly in a weight ratio of 95:2.5:2:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer until the mixed system becomes a positive electrode slurry with uniform fluidity;

[0066] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at 85°C, cold pressed, trimmed, cut and slit, and dried at 85°C for 4 hours under vacuum conditions. The tabs are welded to obtain positive electrode sheets.

[0067] 4. Lithium battery assembly

[0068] The negative electrode sheet, the positive electrode sheet and the isolation film are stacked, packaged, injected with liquid (EC: DMC = 1: 1 vol%), and then packaged again to obtain a lithium-ion battery.

[0069] Example 3

[0070] 1. Preparation of negative electrode slurry

[0071] The negative electrode slurry is prepared by the following steps:

[0072] S1, mixing a first binder with deionized water to obtain a glue solution; mixing the negative electrode active material with the first conductive agent for 40 minutes to obtain a powder mixture;

[0073] S2, mixing the powder mixture with the glue, and then mixing with the second conductive agent, stirring for 1.5 hours, and continuing to add the second binder to adjust the viscosity to obtain a conductive mixture;

[0074] S3, mixing the conductive mixture with the additive, adjusting the viscosity to 4500 cps, and stirring to obtain negative electrode slurry.

[0075] 2. Preparation of negative electrode

[0076] The above-mentioned negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at 85°C, and then cold pressed, trimmed, cut into pieces, and slit. After slitting, it is dried at 85°C under vacuum conditions for 4 hours, and the pole ears are welded to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. In the negative electrode active material layer, the mass ratio of the additive (propylene sulfonic acid), the binder (the mass ratio of polyacrylic acid and styrene-butadiene rubber is 5:1), the conductive agent (the mass ratio of acetylene black and vapor-grown carbon fiber is 10:1), and the negative electrode active material (the mass ratio of graphite and silicon is: 90:10) is 0.3:1.5:1.5:96.7.

[0077] 3. Preparation of positive electrode

[0078] Positive electrode sheet preparation: positive electrode active material LiMn 0.6 Fe 0.4 O4, binder polyvinylidene fluoride (PVDF), conductive agent carbon black, and conductive agent carbon nanotubes are mixed evenly in a weight ratio of 95:2.5:2:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer until the mixed system becomes a positive electrode slurry with uniform fluidity;

[0079] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at 85°C, cold pressed, trimmed, cut and slit, and dried at 85°C for 4 hours under vacuum conditions. The tabs are welded to obtain positive electrode sheets.

[0080] 4. Lithium battery assembly

[0081] The negative electrode sheet, the positive electrode sheet and the isolation film are stacked, packaged, injected with liquid (EC: DMC = 1: 1 vol%), and then packaged again to obtain a lithium-ion battery.

[0082] Example 4

[0083] The difference between this embodiment and embodiment 1 is that the mass ratio of the first binder to the second binder is 11:1; the remaining steps and parameter settings are consistent with those of embodiment 1.

[0084] Example 5

[0085] The difference between this embodiment and embodiment 1 is that the mass ratio of the first binder to the second binder is 1:11; the remaining steps and parameter settings are consistent with those of embodiment 1.

[0086] Example 6

[0087] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the second conductive agent is 22:1; the remaining steps and parameter settings are consistent with those of embodiment 1.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the second conductive agent is 1:1.5; the remaining steps and parameter settings are consistent with those in embodiment 1.

[0090] Example 8

[0091] The difference between this embodiment and embodiment 1 is that the additives are sodium dodecyl sulfate and sodium 2-ethylhexyl sulfate in a mass ratio of 5:5; the remaining steps and parameter settings are consistent with those in embodiment 1.

[0092] Example 9

[0093] The difference between this embodiment and embodiment 1 is that the additives are sodium dodecyl sulfate and propylene sulfonic acid in a mass ratio of 5:5; the remaining steps and parameter settings are consistent with those in embodiment 1.

[0094] Example 10

[0095] The difference between this embodiment and embodiment 1 is that the additives are sodium dodecyl sulfate, sodium 2-ethylhexyl sulfate and propylene sulfonic acid in a mass ratio of 6:2:2; the remaining steps and parameter settings are consistent with those in embodiment 1.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that the negative electrode active material layer does not contain additives; the remaining steps and parameter settings are consistent with Example 1.

[0098] Test Method

[0099] 1. DC internal resistance test

[0100] The impedance of the lithium batteries in the above embodiments and comparative examples was tested: the specific test steps are as follows: at 25°C, the voltage range was set to 2.5-4.2V, 0.33C constant current and constant voltage charging was used to charge to 4.2V, 0.05C was cut off, and then 0.33C was used to discharge to 50% SOC. After standing for 1h, it was discharged at 1C for 10s, and the voltage after standing and after 10s discharge was recorded. The DC internal resistance of 10s was calculated and the data was recorded in Table 1.

[0101] 2. Lithium battery cycle life test

[0102] The lithium batteries in the above embodiments and comparative examples were subjected to a lithium battery cycle performance test. The specific test steps are as follows: at 25°C, the voltage range is set to 2.5-4.2V, the prepared lithium batteries are charged and discharged at a 1C rate, and a full charge and discharge cycle test is performed for 1000 cycles, and the capacity retention rate is recorded in Table 1.

[0103] 3. Lithium battery capacity performance test

[0104] The lithium batteries in the above embodiments and comparative examples were subjected to lithium battery cycle performance tests. The specific test steps are as follows: at 25°C, the voltage range is set to 2.5-4.2V, the prepared batteries are charged and discharged at a rate of 0.33C, and the first cycle charge and discharge capacity is recorded in Table 1.

[0105] 4. Lithium battery storage life test

[0106] The lithium batteries in the above embodiments and comparative examples were subjected to a lithium battery cycle performance test, and the specific test steps are as follows: at 25°C, the voltage range is set to 2.5-4.2V, the prepared lithium battery is charged to 4.2V at 0.33C constant current and constant voltage, and cut off at 0.05C, and is placed in a 60°C incubator for storage, and then the voltage is recorded every 7 days, and the battery is recharged to 100% SOC and stored for 30 days, and the capacity retention rate is recorded in Table 1.

[0107] Table 1

[0108] Serial number DC internal resistance / mΩ Cycle capacity retention rate / % First cycle discharge capacity / mAh Capacity retention rate / % Example 1 25.6 73 1502 85 Example 2 26.3 75 1503 87 Example 3 25.5 72 1508 84 Example 4 25.8 71 1510 88 Example 5 27.3 74 1505 83 Example 6 27.8 72 1503 82 Example 7 27.9 71 1504 81 Example 8 25.4 76 1506 87 Example 9 25.5 75 1507 86 Example 10 25.3 76 1508 88 Comparative Example 1 28.4 68 1501 71

[0109] In combination with Examples 1-3, Comparative Example 1 and Table 1, it can be seen that by introducing additives into the negative electrode active material layer, the DC resistance of the lithium battery is reduced, the cycle capacity retention rate is increased, and the storage life is extended. This is because the additives can form a uniform active material layer on the surface of the negative electrode current collector through the effects of electrostatic repulsion and steric hindrance, making the current density more uniform, so that a relatively uniform SEI film can be formed at the negative electrode, avoiding the phenomenon of lithium dendrites piercing the diaphragm due to the dissolution of positive electrode metal ions at the negative electrode, and can also make the transition metal ions better spread on the surface of the negative electrode current collector, significantly improving the storage stability of the lithium battery.

[0110] In combination with Example 1, Examples 4-5 and Table 1, it can be seen that when the mass ratio of the first binder to the second binder is too high or too low, it is not conducive to the uniform dispersion of the active material particles in the negative electrode slurry. On the other hand, it is not conducive to the uniform dispersion of the additive in the negative electrode slurry, thereby reducing the promoting effect of the additive on promoting the uniform deposition of the negative electrode slurry, and the lithium battery cycle performance and storage stability are slightly reduced.

[0111] In combination with Example 1, Examples 6-7 and Table 1, it can be seen that by adjusting the mass ratio of the first conductive agent to the second conductive agent to remain within a suitable range, it is also helpful to reduce the internal resistance of the lithium battery and improve the cycle capacity retention rate of the lithium battery.

[0112] In combination with Examples 1-3, Examples 8-10 and Table 1, it can be seen that by further optimizing the types and dosage ratios of additives, it is helpful to maintain the internal resistance of the lithium battery at a low level and significantly improve the cycle capacity retention rate and storage stability of the lithium battery.

[0113] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises an additive and a negative electrode active material, and the mass ratio of the additive to the negative electrode active material is 0.01-5:100; Wherein, the additive includes at least one of sodium sulfonate, sulfate and sulfonated olefin.

2. The negative electrode sheet according to claim 1, characterized in that: The sodium sulfonate salt comprises at least one of sodium dodecylbenzene sulfonate, sodium sulfosuccinate, sodium diethyl sulfosuccinate, and sodium dipentyl sulfosuccinate; The sulfate includes at least one of sodium ethylhexyl sulfate, sodium 2-ethylhexyl sulfate, 2-ethylhexyl sulfate ester salt, 2-ethylhexyl sulfate ester salt, lauryl ether sulfate, and polyoxyethylene alkylphenol ether sodium sulfate; The sulfonated olefin includes at least one of propylene sulfonic acid, sulfonamide, and sulfonimide.

3. The negative electrode sheet according to claim 1, characterized in that: In the additive, the mass proportion of the sodium sulfonate salt is 50%-60%.

4. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material layer also includes a binder, and the mass ratio of the binder to the negative electrode active material is 0.5-10:

100.

5. The negative electrode plate according to claim 4, characterized in that: The binder includes a first binder and a second binder, wherein the first binder includes at least one of sodium carboxymethyl cellulose and polyacrylic acid; and the second binder includes at least one of styrene-butadiene rubber and polyacrylic acid.

6. The negative electrode plate according to claim 5, characterized in that: The mass ratio of the first binder to the second binder is 10:1-1:

10.

7. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material layer also includes a conductive agent, and the mass ratio of the conductive agent to the negative electrode active material is 0.5-10:

100.

8. The negative electrode plate according to claim 7, characterized in that: The conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes at least one of conductive carbon black, artificial graphite, and acetylene black; and the second conductive agent includes at least one of carbon nanotubes and vapor-grown carbon fibers.

9. The negative electrode sheet according to claim 8, characterized in that: The mass ratio of the first conductive agent to the second conductive agent is 20:1-1:

1.

10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet as claimed in any one of claims 1 to 9.